Hak Asasi Manusia (Ham) pada Kebebasan Berpendapat/Bereksperesi dalam Negara Demokrasi di Indonesia - Wahyuni, Rizki; Yati Sharfina Desiandri (Universitas Medan Area, 2024)
The aim of this research is to clarify the rights and position of human rights and freedom of opinion in the 1945 Constitution towards a democratic state in Indonesia. This research method is library research, which is a normative juridical approach method in legal research or library legal research, namely an approach that establishes legal rules as provisions and is based on basic law. The results of this research are regarding freedom of opinion in a democratic country in Indonesia which is regulated in the 1945 Constitution, namely the right to hold opinions, express opinions and form associations (1945 Constitution Article 28 E, F), which shows that freedom of opinion is the right to think and express opinions. Law Number 39 of 1999 concerning Human Rights is contained in Articles 14, 23, 24 and 25. Law Number 9 of 1998 confirms that freedom of opinion is a basic right in life which is guaranteed and protected by the State. Currently, freedom of opinion is sometimes only granted in response to constructive criticism from the general public, but freedom of opinion, both oral and written, is often restricted in the public sphere.